Protesters as terrorists? - Terwindt, Carolijn (Crime, law and social change, 2014)
The attack on the World Trade Center in September 2001 in New York has led to a worldwide increase in anti-terrorism legislation and much debate about the proper (legitimate, proportional and effective) response to the perceived threat of mass casualty attacks. In practice, however, anti-terrorism legislation is frequently applied in criminal cases that are unrelated to such mass casualty attacks. Instead, terrorism charges are leveled against conduct that was previously not categorized as terrorism and which is not always easy to distinguish from ordinary crimes, civil disobedience or legitimate protest activities, such as aggressive leafleting, sabotage of machinery, arson and offensive speech. This article explores the political process behind the categorization of such conduct as "terrorism" and the expanded scope of anti-terrorism legislation in the United States, Spain and Chile. Based on ethnographic fieldwork and the analysis of cases in which conduct is newly charged as terrorism, the author shows that these charges are the result of a deliberate campaign by groups in society that feel neglected by the government and appeal to the terrorism label in their demand for better protection.